Deposits in Wood Micro-Structures of Some Wood Species - Adeniyi, I. M; Areghan, S.E.; Alao, O.J.; Salaudeen, G. T; Falemara, B.C (Richtmann Publishing, 2012)
Implications of wood deposits in processing and utilization of wood species of Terminalia superba, Daniellaogea, Distemonanthus benthamianus, Afromesia elata, Mansonia altissima, Tectona grandis, Gmelinaarborea, Afzelia Africana, Pterocarpus soyauxii, Guara cedrata, Holoptelea grandis Khaya ivorensi, andGossweilerodendron bassalmiferun were investigated in this study. Wood deposits such as resins, gum,crystals, silica, tannins and oils are usually deposited in the wood microstructures (e.g, parenchyma cells)thereby making it impossible for end users to assign wood for certain uses. When in abundance thedeposits could pose a great threat during wood processing such as causing dulling effect on saws, difficultyin preservative absorption, inability to bond with other adhesives during board and laminated itemsproduction, and staining thereby reducing the aesthetic value of the wood. Some wood species not suitablefor cement-bounded were found to be blocked with some deposits such as gum deposits. However, somedeposits (tannins, resins and oils) identified in some wood species have made such woods useful in someindustries such as leather industry making them of industrial importance and are found useful whenabundantly present wood; some wood deposits also confer beauty and also protect wood against biodeterioratingagents such as termites and beetles. This study revealed the presence of such deposits andtheir implication on wood processing and utilization; photomicrographs showing their various positions inwood micro-structure are also presented.